Hong Kong: SARS in the SAR, A Tale of Four Buildings. Issue 5 (1st October 2004) - Kay, Richard
Abstract : The Hong Kong Special Administrative Region (SAR) is one of two SARs, the other being Macau, set up by China at the end of the 20th century to administer the last two returned colonies, from Britain and Portugal, respectively. Like no other city in communist China, the two SARs are to be allowed to continue with their capitalist way of life for 50 years. For Hong Kong, that has meant that all the institutions that were in place before 1997, such as its civil service and legislative council, have remained in operation after the takeover. The few visible changes include the governor (now called the Chief Executive), the flag, the military (now confined to barracks), and the opting-out of royal patronage for the likes of the Jockey and Golf Clubs. In matters of health Hong Kong has, since the 1970s and 80s, enjoyed all the trappings of a first-world city.